2014
DOI: 10.1007/978-1-4939-0669-7_14
|View full text |Cite
|
Sign up to set email alerts
|

A Solid-Phase Assay for Studying Direct Binding of Progranulin to TNFR and Progranulin Antagonism of TNF/TNFR Interactions

Abstract: The discovery that TNF receptors (TNFR) serve as the binding receptors for progranulin (PGRN) reveals the significant role of PGRN in inflammatory and autoimmune diseases, including inflammatory arthritis. Herein we describe a simple, antibody-free analytical assay, i.e., a biotin-based solid-phase binding assay, to examine the direct interaction of PGRN/TNFR and the PGRN inhibition of TNF/TNFR interactions. Briefly, a 96-well high-binding microplate is first coated with the first protein (protein A), and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 28 publications
(25 reference statements)
1
27
0
Order By: Relevance
“…51,60 Deletion mutants of TNFR1 and TNFR2 used to map the binding of PGRN revealed that CRD2 and CRD3 of TNFR are essential for the interaction with PGRN, similar to the binding to TNFa. 55,56,61,62 In conclusion, our present study revealed that administration of PGRN attenuated insulin signaling and triggered ER stress in vivo and in vitro studies, with such effects being drastically reversed by PBA, suggesting a causative role of ER stress in PGRN-induced impaired insulin sensitivity and implicated that decreasing PGRN levels by influencing its turnover or production is consequently a promising therapeutic approach applied to metabolic disorders.…”
Section: Discussionsupporting
confidence: 53%
“…51,60 Deletion mutants of TNFR1 and TNFR2 used to map the binding of PGRN revealed that CRD2 and CRD3 of TNFR are essential for the interaction with PGRN, similar to the binding to TNFa. 55,56,61,62 In conclusion, our present study revealed that administration of PGRN attenuated insulin signaling and triggered ER stress in vivo and in vitro studies, with such effects being drastically reversed by PBA, suggesting a causative role of ER stress in PGRN-induced impaired insulin sensitivity and implicated that decreasing PGRN levels by influencing its turnover or production is consequently a promising therapeutic approach applied to metabolic disorders.…”
Section: Discussionsupporting
confidence: 53%
“…CTRP‐3 is an adipokine involved in adipogenesis and as a pleiotropic factor in metabolic and immunological processes which has been described to be inversely associated with BMI and metabolic syndrome . Further being well‐known for its anti‐inflammatory properties, CTRP‐3 thus resembles progranulin which has been described as an anti‐atherosclerotic factor and as an inhibitor of pro‐inflammatory TNF signalling . Similar to a potential inhibition of TNF‐induced pro‐inflammatory signalling by progranulin, CTRP‐3 has been demonstrated to antagonize LPS‐ and TNF‐induced inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…also have reported that Il-6 can activate the ERK1/2/RSK1/C/EBPβ pathway and PGRN synthesis as a consequence (21). Furthermore, several studies have shown that PGRN may antagonize TNF-α by the activation of its receptors, therefore PGRN may have some anti-inflammatory properties (22). Studies have also regarded TNF-α as an inhibitor of osteoblast differentiation, as well as an activator of osteoclastogenesis (23).…”
Section: Discussionmentioning
confidence: 99%